Effects of individual or combined use of alpha-lipoic acid and methylprednisolone on malondialdehyde, superoxide dismutase, and catalase levels in acute spinal cord injury in rats (Journal of Health Sciences, 2016)
Introduction: Recent studies have demonstrated that alpha-lipoic acid (ALA) has a strong antioxidant property and it exerts neurotrophic effects on the peripheral nerves. In this study, we investigated potential effects of ALA on secondary injury mechanisms as well as on apoptosis.Methods: Forty Sprague-Dawley rats were equally divided into 5 groups, as follows: laminectomy (control), laminectomy + trauma (Trauma), laminectomy + posttraumatic methylprednisolone [MP] (Trauma + MP), laminectomy + posttraumatic ALA (Trauma + ALA), laminectomy + posttraumatic MP and ALA (Trauma + MP + ALA). Yasargil aneurysm clip method was used to induce the spinal cord injury. Twenty-four hours after the procedure the rats were sacrificed. Spinal cord samples were harvested to analyze malondialdehyde (MDA), superoxide dismutase (SOD), and catalase (CAT) levels, as well as histopathological characteristics.Results: The Kruskal-Wallis test (95% confidence level, p < 0.05) showed a statistically significant difference between the groups in MDA (p = 0.006), CAT (p = 0.000), and SOD (p = 0.001) levels. Pairwise comparisons, with Bonferroni correction, of control and Trauma group with the other groups, revealed a significant difference in CAT and SOD levels. Overall, our results showed that ALA administration significantly decreased MDA levels in Trauma + ALA compared to the same effect of MP in Trauma + MP group. Furthermore, ALA administration increased SOD and CAT levels in Trauma + ALA group. The combined use of ALA and MP demonstrated synergistic effects and yielded even more significant results.Conclusions: A combined use of ALA and MP might provide a benefit in patients exposed to spinal cord injury. However, at present, further studies are required to confirm these results.